CHAMBER GRAVES AND THEIR IMITATIONS ON THE RIGHT BANK OF THE DNIPER: WAYS OF EVOLUTION OF THE ELITE FUNERAL RITE (City: History, Culture, Society, 2021)
The article is devoted to a specific category of ancient Rus burial monuments of X–XI centuries. They combine the features of both elite chamber tombs of the Viking Age and ordinary Christian burials of the beginning of the II millennium AD. The author considered to combine such burials under the term “pseudo-chambers” or “imitation chambers”. There are four types of them: 1) chambers with coffins; 2) ground chambers; 3) “earthen” chambers with wooden flooring, but without wall coverings; 4) “large burial pits” without wooden structures. In the article, there is the analysis of the structural and ceremonial features of each of these chamber types. Moreover, the author identifies their peculiarities.Obviously, the erection of classical chamber tombs in the southern Rus territories ceased with the beginning of Christianization. However, the ancient Rus elite could not abandon this tradition completely, which was reflected in the appearance of imitation cameras. The vast majority of them inside permanent wooden structures contain a movable coffin. This fact contradicts the basic idea of the classical chamber tombs as “houses of the dead” and indicates at least a significant influence of the Christian doctrine. The spread of pseudo-chambers in the territory of Volyn should undoubtedly be linked to the governmental activity of Volodymyr Sviatoslavych that may have been accompanied by an influx of people (“greater men”) from the Middle Dnieper. According to the composition of the funerary inventory and analogies from the adjacent territories, they can be dated from the end of X – the first half of XI centuries.Comprehensive analysis of construction features and funerary inventory of imitation chambers does not allow us to uniquely associate them with representatives of the ancient Rus elite. Within the region, mentioned monuments are not a direct line of development of classical chamber tombs, but merely imitate socially prestigious ceremonial elements of the latter.
Keywords: Ancient Rus; right bank of the Dnieper; funeral rite; flexed position